Quantum capacitance transient phenomena in high-k dielectric armchair graphene nanoribbon field-effect transistor model. (October 2021) - Avnon, Asaf; Golman, Roman; Garzón, Esteban; Ngo, Ha-Duong; Lanuzza, Marco; Teman, Adam
Highlights: Quantum capacitance becomes dominant with high-k ultra-thin dielectrics. Quantum capacitance in Nanoribbons is influenced by Van-Hove singularities. The transient mode in an armchair graphene nanoribbon field-effect transistor results in undulations. An extended Verilog-A model was built to include the quantum capacitance influence. Abstract: Graphene Nanoribbons (GNRs) are an emerging candidate to challenge the place of current semiconductor-based technology. In this work, we extend a model for Armchair Graphene Nanoribbons Field-Effect Transistor (AGNRFET) to the high-k dielectrics realm and examine the influences of quantum capacitance on its transient phenomena. The model is coded with Verilog-A and evaluated through SPICE simulations. We have considered a comparison between the extended model with and without the influence of the quantum capacitance. Simulation results show a realistic scenario where influence of the quantum capacitance significantly impacts the transient behaviour in circuit design. This proves the proposed model to be a valuable aid for the circuit design of future graphene-based applications.